A long-life nano-silicon anode for lithium ion batteries: supporting of graphene nanosheets exfoliated from expanded graphite by plasma-assisted milling - Sun, Wei; Hu, Renzong; Zhang, Hanyin; Wang, Yukun; Yang, Lichun; Liu, Jiangwen; Zhu, Min (Electrochimica acta, 2016)
In order to enhance the cycleability and electronic conductivity of Si-based anodes, we fabricated a hierarchical micro-nano structured silicon/graphene nanosheets (Si/GNs) hybrid by discharge plasma-assisted milling (P-milling) using Si nanoparticles and expanded graphite (EG) as starting materials. Owing to the synergistic effect of rapid plasma heating and ball mill grinding with Si nanoparticles as nanomiller, the graphene nanosheets was exfoliated efficiently from the loose structured EG, which tightly wrapped and connected the Si nanoparticles to form microsized composite agglomerates. This high powder tap density Si/GNs hybrid exhibited a high reversible capacity of 942mAhg−1 (857mAhcm−3) at the current density of 0.2Ag−1, with 88% capacity retention after 100 cycles. The charge capacity remained super stable more than 350 times when the electrode was cycled with a fixed lithiation capacity of 1000mAhg−1 at a current density of 0.2Ag−1 between 0.01 and 1.5V (vs. Li/Li+). This superior cycle performance was attributed to the microsized GNs matrix which facilitated the electronic conductivity and the Li+ diffusion in the hybrid, and effectively accommodated the volume change of Si nanoparticles during Li+ alloying and dealloying processes.